Level of Satisfaction of Faculty Members: Its Relationship to Their Levels of Commitment, Professionalism and Performance - Nicolas, Prince Mert O.; Leona, Rodibelle F.; Carlos, Christine Joyce M.; Cochanco, Rose Anne G. (International Journal of Scientific Research and Management (IJSRM), 2024)
Faculty satisfaction plays a critical role in the overall success of educational institutions, impacting not only faculty retention but also their levels of commitment, professionalism, and performance. This study examines the relationship between faculty satisfaction and these key factors among the faculty members of the College of Information and Communications Technology (CICT) at the Nueva Ecija University of Science and Technology (NEUST). Using a quantitative research design, data was collected from 31 faculty members through surveys measuring satisfaction, commitment, professionalism, and performance. The results revealed that faculty members exhibit high levels of satisfaction, particularly in areas such as job security, compensation, and institutional support for professional development. Correlation analyses showed significant positive relationships between satisfaction and commitment (r=0.44), professionalism (r=0.73), and performance (r=0.68). These findings suggest that enhancing faculty satisfaction could lead to improved commitment, ethical behavior, and academic performance, thus contributing to the overall effectiveness of the institution. The study recommends implementing work-life balance initiatives, recognition programs, and continuous professional development to further boost faculty satisfaction and institutional success.